Hypoxia-inducible factor-1α gene polymorphisms in early and late onset preeclampsia in Sinhalese women - Andraweera, P.H.; Dekker, G.A.; Thompson, S.D.; Dissanayake, V.H.W.; Jayasekara, R.W.; Roberts, C.T. (Placenta (Eastbourne), 2014)
Early (EPE) and late (LPE) onset preeclampsia are increasingly being recognized as two distinct disorders. Placental vascular defects are more common in EPE. Hypoxia Inducible Factor 1α (HIF1α) regulates the expression of many angiogenic growth factors in the placenta. We studied the association of two polymorphisms in the HIF1α gene (rs11549465 and rs10873142) with EPE and LPE. 175 nulliparous Sinhalese women with preeclampsia and 171 normotensive women matched for age, ethnicity, parity and BMI were recruited at two tertiary care hospitals in Colombo. Preeclampsia was diagnosed using international guidelines. DNA extracted from peripheral blood was genotyped using Sequenom MassARRAY. HIF1α rs11549465 dominant model and T allele were reduced in women who developed EPE compared to controls [P = 0.002, OR (95% CI) = 0.3 (0.1–0.7)], in preeclamptic women who delivered small for gestational age babies [P = 0.02, OR (95% CI) = 0.5 (0.2–0.9)] compared to controls and in women who developed EPE compared to those who developed LPE [P = 0.006, OR (95% CI) = 0.3 (0.1–0.7)]. Our results demonstrate a protective effect of the T allele in LPE and normal pregnancy, which is relatively lacking in EPE due to low prevalence of this protective allele. HIF1α rs11549465 T allele was previously demonstrated to be associated with a higher transcriptional activity and increased angiogenesis. Inherited susceptibility to increased HIF1α expression resulting in the up-regulation of angiogenic genes may mediate a protective effect in normal pregnancy and pregnancy complicated by LPE. •Early and late onset preeclampsia are now recognized as two distinct disorders.•HIF1-α regulates many vital molecular pathways during early placentation.•HIF1α rs11549465 was investigated in women with early and late onset preeclampsia.•The T allele is protective in normal pregnancies and in late onset preeclampsia.